The Application of Porous Material in the Capillary Barrier System for Residual Soil Slope Stabilization - Baharudin, Nur Azlin; Kassim, Azman; Ahmad, Kamarudin; Sirat, Qurratu Aini (Trends in Sciences, 2023)
A drainage system that is used to flow excess rainfall infiltration is an excellent alternative to enhance lateral diversion capacity at the interface of Grade VI and Grade V soil slope layers thus delaying breakthrough occurrences. This study aims to explore the performance of porous transport layer on slope behavior via numerical simulation by GeoStudio SEEP/W. In this study, a 2-dimensional non-homogenous residual soil configuration model, which is composed of Grade VI and Grade V residual soil was constructed. Laboratory tests were conducted on the soil samples collected from the Faculty of Engineering, UTM JB to determine the soil properties as input parameters in numerical modeling. The soil slope model is designed as an infinite residual soil slope according to Jabatan Kerja Raya (JKR) design specification on the cut slope and fill slope with 27 ° inclination respectively. High rainfall intensities were chosen to represent rainfall infiltration in Johor. The slope model was modeled with a porous transport layer at the Grade VI and Grade V layer interfaces. The porous transport layer is introduced as the transport layer and its effectiveness is expected to be similar to the optimum compacted soil mix in the previous study. In addition, porous concrete as a transport layer is introduced and it must meet the adequate porosity and hydraulic conductivity requirements. The suction distribution pattern with depth and time was subsequently observed to identify the volume of infiltrated water and retention time in the transport layer. The porous transport layer is also expected to be efficient in diverting infiltrating water and decreasing the interface’s suction distribution between Grade VI and Grade V soil layers. HIGHLIGHTS The water built up within the residual soil slope is one of the common factors of rainfall-induced residual soil slope failure thus porous transport layer introduced The detailed laboratory testing and numerical modelling conducted in order to identify the performance of porous transport layer within residual soil slope The application of porous transport layer sandwiched between residual soil is effective to decrease the water built up and matric suction thus decrease the risk of slope failure GRAPHICAL ABSTRACT